2018
DOI: 10.3390/toxins10090378
|View full text |Cite
|
Sign up to set email alerts
|

The Streptococcus pneumoniae yefM-yoeB and relBE Toxin-Antitoxin Operons Participate in Oxidative Stress and Biofilm Formation

Abstract: Type II (proteic) toxin-antitoxin systems (TAs) are widely distributed among bacteria and archaea. They are generally organized as operons integrated by two genes, the first encoding the antitoxin that binds to its cognate toxin to generate a harmless protein–protein complex. Under stress conditions, the unstable antitoxin is degraded by host proteases, releasing the toxin to achieve its toxic effect. In the Gram-positive pathogen Streptococcus pneumoniae we have characterized four TAs: pezAT, relBE, yefM-yoeB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 76 publications
2
43
0
Order By: Relevance
“…Gram-positive bacteria also encode YoeB-YefM TA systems. In Streptococcus pneumoniae, a chromosomal YoeB module is toxic when expressed in E. coli and has been associated with tolerance to oxidative stress and contributions to biofilm formation in its native host (Nieto et al, 2007;Chan et al, 2018). This toxicity is similar to results obtained with the highly similar YoeB-YefM system from Streptococcus suis (Zheng et al, 2015).…”
Section: Introductionsupporting
confidence: 75%
“…Gram-positive bacteria also encode YoeB-YefM TA systems. In Streptococcus pneumoniae, a chromosomal YoeB module is toxic when expressed in E. coli and has been associated with tolerance to oxidative stress and contributions to biofilm formation in its native host (Nieto et al, 2007;Chan et al, 2018). This toxicity is similar to results obtained with the highly similar YoeB-YefM system from Streptococcus suis (Zheng et al, 2015).…”
Section: Introductionsupporting
confidence: 75%
“…This study found, first, that the RelBE2 complex positively regulates the promoter activity ( Figure 6 B), while the RelBE of other bacteria negatively regulates the promoter activity [ 49 , 53 , 60 , 61 ]. Considering that type II TA systems contribute to the formation of persistence cells, stress response, biofilm formation and other various biological processes [ 13 , 15 , 31 , 62 , 63 , 64 ], the mechanism of three TA systems in S. suis 2 remains to be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of yefM-yoeB, relBE or all TA systems in strain R6 sensitizes these bacteria to oxidative stress; in addition, biofilm formation is significantly impaired, though the growth rate is not significantly affected. These results indicate that two pairs of TA systems in pneumococci perform the same role, similarly contributing to bacterial oxidative stress and biofilm formation [44]. Therefore, we can speculate that when environmental stressors are removed, the newly synthesized antitoxin of a pathogen TA system will complex with the existing cognate or a different source of toxin to reverse toxicity, restore normal growth, and promote adaptation.…”
Section: A Type II Ta System Cross-regulates the Transcription Of Itsmentioning
confidence: 92%